2018
DOI: 10.3126/nepjoph.v9i2.19270
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous formation and closure of full thickness macular hole in a vitrecto-mised eye : a case report

Abstract: The exact pathogenesis of macular hole (MH) is controversial with most of the cases being idiopathic. Trauma is an important cause of secondary MH formation. MH post Pars Plana Vitrectomy (PPV) is an even rare entity with only a handful of cases reported so far ( Kumagai et al, 2008; Smiddy W.E, 1993; Kimura et al, 2005). An even rarer event is spontaneous closure of post PPV full thickness macular hole (FTMH), though spontaneous closure of traumatic macular hole (TMH) has been reported before. Herein, we repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Observation of MH and monitoring hoping for self-closure of the MH is a strategy, and there have been reports of spontaneous closure of the MH with improvement in BCVA. 8 In our study, case 5 demonstrated OCT features of attempted spontaneous hole closure while waiting for MH surgery, as seen in Figure 9 . Lastly, we should mention that topical treatment of secondary MH has been reported with anatomical success and improvement in vision.…”
Section: Discussion and Reviewmentioning
confidence: 50%
See 2 more Smart Citations
“…Observation of MH and monitoring hoping for self-closure of the MH is a strategy, and there have been reports of spontaneous closure of the MH with improvement in BCVA. 8 In our study, case 5 demonstrated OCT features of attempted spontaneous hole closure while waiting for MH surgery, as seen in Figure 9 . Lastly, we should mention that topical treatment of secondary MH has been reported with anatomical success and improvement in vision.…”
Section: Discussion and Reviewmentioning
confidence: 50%
“…Another mechanism of MH formation is iatrogenic trauma during vitrectomy surgery. 8 Possible causes of iatrogenic trauma include direct instrument contact, traction induced MH during ILM or ERM peeling, and the direct impact of a jet of high-velocity air or infusion fluid on the macula. A replay of the surgical video, if available, will reveal any unrecognized physical impact on the macula.…”
Section: Discussion and Reviewmentioning
confidence: 99%
See 1 more Smart Citation